FREYRE POR QUINTAS: : A REVIEW OF THE WORK “SEX IN PATRIARCHAL FASHION” - Vieira Cavalcanti, Luíza; Valdevino do Amaral, Walter (Revista Gênero e Interdisciplinaridade, 2022)
In this paper, we propose to establish an analysis of the book “Sex à Moda Patriarchal: the feminine and the masculine in the work of Gilberto Freyre” (2008). It is a text by the anthropologist Fátima Quintas, where she proposes to analyze the relationships between men and women during the colonial period, described in the books by the sociologist Gilberto Freyre. With the text, Quintas try to problematize not only the sexual relations that took place in a phallocentric society, but also how aspects of femininity are seen and treated within the same patriarchal environment. Through the reading, it is also possible to identify how Freyre is read by the anthropologist, as well as the relationship she establishes with him. From our study, therefore, we search to present a critical parameter about the author’s surveys and interconnections between History, gender studies and academic literature. We take as theoretical-methodological contributions to the development of this research, the historian Joan Scott and the philosopher Judith Butler, with their contributions to gender studies; and, the historian Roger Chartier, for the study and understanding of the work-author relationship.